Introduction to the Musical Compotition “Giri Petak” | Pengantar Komposisi “Giri Petak” - Ida Bagus Kadek Sudana Astika Manuaba (GHURNITA: Jurnal Seni Karawitan, 2023)
"Giri" means mountain, and "Plot" means white or white light. So, Giri Petak is a white light or holy light that comes from the mountain (Mount Agung), giving birth to a spiritual spirit that will eventually create prosperity. In other words, Giri Petak is the religious spirit of Mount Agung. This innovative creation of tabuh depicts a spiritual spirit based on the love or affection of an individual inspired by the literary development carried out by the community or residents at the foot of Mount Agung, namely "Gebang Apit Lontar". This innovative tabuh creation is contemporary by prioritizing originality and referring to traditional patterns or standards performed using the Semara Pegulungan Saih Pitu media. The creation method used in creating karawitan works of art is divided into three stages, namely the Assessment (Exploration) Stage, in which the writer looks for inspiration for this karawitan artwork. In the Trial Stage (Improvisation), the writer begins to compose the piece from the concept the author has adopted, and in The Forming Stage, the author continues pouring the music from part 1 to part 4.